Bioactive compounds, antidiabetic and antimicrobial potential of pinang seeds extract (Areca catechu l) - Suryowati, Trini; Siagian, Forman Erwin; Maheshwari, Hera; Diani, Yusias Hikmat; Kusuma, Rini Anjarwati (Universitas Aisyah Pringsewu, 2023)
Diabetes mellitus is a chronic metabolic disorder affecting people of all ages. The critical aspect of fruits is that rich sources of antioxidants may act in combination with each other phytochemicals to provide their protective effect. Pinang (Areca catechu L.) fruit is edible as the local indigenous plant from West Irian Jaya (Papua) Indonesia. This study was aimed at investigating the biologically active compounds of seeds, fruits, and leaves, the a-glucosidase inhibitory and antibacterial activity of seeds of Pinang against Gram-positive bacteria Staphylococcus aureus ATCC 25923, and Gram-negative bacteria Escherichia coli ATCC 25922. Pinang fruits were extracted by using the maceration method and ethanol solvent. Identify the chemical compounds in seeds by GC-MS technique, test to a-glycosidase inhibitory effect was measured with spectrophotometric. Well, the diffusion method was employed in evaluating the antimicrobial property of extracts. The evaluation of the bioactive compound of Pinang fruits revealed the presence of Vitamin E (0.20%). The inhibition of a-glucosidase of seeds extract of IC50 values was 82.74 ppm, and the global standard was 0.34 ppm. This study confirmed that Pinang seeds contain glucosidase activity that has the potency to inhibit glucose. The antimicrobial activity was performed against bacteria as it showed zone inhibition. These results indicated that Pinang seed extracts exerted potent inhibitory effects against a-glucosidase and inhibited the proliferation of Gram-negative microorganisms.